Efeito da orientação para perda de peso em pacientes inférteis com sobrepeso e obesidade - Benetti, Beatriz Bacheschi do Carmo (2022)
Introduction: Obesity is considered a worldwide epidemic, being a serious public health problem. Overweight and obesity are characterized by the accumulation of body fat that poses a health risk. Several pathophysiological disorders are caused by obesity, especially in people with Body Mass Index (BMI) above 30 kg/m². It is increasingly common among women of childbearing age. Obese women are three times more likely to suffer from infertility than women with a normal body mass index. Objective: Evaluate the response to weight loss guidance in anthropometric parameters of obese and overweight infertile patients undergoing assisted fertilization treatment (high and low complexity). Methods: Retrospective cohort. A survey was carried out of a population of overweight and obese infertile patients one to two years after the first visit. In the first consultation at the assisted reproduction clinic (Human Reproduction Laboratory HC / UFG) as obese and overweight patients were instructed to lose weight and information that excess weight could decrease as chances of being successful in the treatment. As endocrine variables, estradiol, FSH, and LH were evaluated between obese and overweight patients in relation to normal weight patients. Proportions were compared using the chi-square test. Medians with the Mann-Whitney test. The H0 Rejection Level was 5%. Results: The age of the patients and the values of FSH, LH and estradiol were evaluated and paired, it was then verified that all presented p>0.05 after the adjustments. The age range of patients ranged from 21 to 40 years, with a mean of 35.59 ± 3.23 for the group with normal BMI and 35.78 ± 3.70dp for the group classified as overweight and obese. The mean weight in kg before and after orientation was 77.11±11.77 and 78.98±12.86 (p<0.0046). The mean BMI (kg/m²) before guidance was 29.69 ± 3.75dp and after guidance was 30.42 ± 4.32 (p<0.0038). Regarding ovulation, 31.6% of patients who lost weight did not ovulate compared to 20.0% of patients who gained weight. Patients who maintained their weight (16.7%) did not ovulate compared to 20.0% of patients who gained weight. Statistically non-significant difference. As for the endocrine variables, FSH, LH and estradiol, when comparing the population with normal weight with the population with overweight and obesity, no significant differences were found. Conclusions: There was a low percentage of weight loss in the patients, as only 37.5% achieved this goal. A greater number of patients gained or maintained their initial weight. Regarding ovulation, no significant associations were found when comparing patients who lost weight and those who gained weight, and also patients who maintained their weight compared to those who gained weight. As for the endocrine variables, in this study, the influence of obesity or overweight on these variables was not detected. The main diagnosis of infertility was bilateral tubal obstruction due to tubal ligation and other causes. Regarding the type of infertility, it was observed that cases of the primary type were the most frequent.